Estudo da interação de FeCl3 e CrO3 nas superfícies dos Nanotubos de InN e GaP utilizando a Teoria do Funcional da Densidade - SILVA, Caio Vinícius Caetano Ribeiro da (2019)
This work presents a theoretical study about the nanotubes of InN and GaP interacting with the compounds FeCl3 and CrO3 through first principles simulations, based on density functional theory (DFT). The calculations were performed with the SIESTA code. Structural, energetic and electronic properties of the FeCl3 and CrO3 compounds adsorbed on the InN and GaP nanotubes were analyzed. The results show that the electronic properties of both nanotubes are affected by the interaction of the FeCl3 and CrO3 compounds. After adsorption of FeCl3, it was observed that the energy gap decreased in both nanotubes, due to appearance of defect levels in the region of the energy gap, however when it was adsorbed internally to the GaP nanotube, the system presented a metallic character. With CrO3, there was an increase in the energy gap when it was adsorbed externally to the GaP nanotube, and in the other systems, the energy gap reduced due to displacements of the energy levels of the valence band. The calculations also indicate that both compounds, adsorbed inside and outside the InN and GaP nanotubes, interact through a chemical adsorption process. In addition, it was observed that when FeCl3 is adsorbed on the InN and GaP nanotubes, it acts as a Lewis acid, whereas CrO3 acts as a Lewis base. A study was also performed about the relativistic effects on the In atom of the InN nanotube, and it was verified through comparisons with results found in the literature that the relativistic correction better describes the electronic properties of this material, but does not alter the trends found in the studied systems.